Coverage and Adherence to Iron Supplement Tablet Consumption Among Female Adolescents in Pekanbaru City, 2023–2025 - Khan, Hafidh Triandha; Mitra, Mitra; Susanti, Melly (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Iron deficiency anemia among adolescent girls remains a significant public health problem with long-term implications for reproductive health and future productivity. One of the national strategies to prevent anemia is the provision of iron–folic acid supplementation, known as iron supplementation tablets; however, its effectiveness largely depends on program coverage and adherence among the target population. This residency study aimed to describe the coverage and adherence of iron supplementation tablet consumption among adolescent girls in Pekanbaru City and to identify factors influencing program implementation. A descriptive qualitative approach was applied through document review of the iron supplementation program reports from 2023–2024, in-depth interviews with nutrition and school health program officers, and direct observation at the Pekanbaru City Health Office. Data were analyzed using a fishbone approach to identify root causes and the Urgency, Seriousness, Growth (USG) method to determine priority problems. The findings indicate that both coverage and adherence to iron supplementation tablet consumption among adolescent girls remain suboptimal, reflected by inadequate follow-up of anemia screening results, weaknesses in recording and reporting systems, limited human resources, and the absence of specific standard operating procedures for adolescent anemia management. In conclusion, strengthening program governance through the development of clear SOPs, capacity building of health personnel, optimization of health information systems, and reinforcement of school and family involvement is essential to improve coverage and adherence to iron supplementation tablet consumption among adolescent girls in Pekanbaru City.